FRIGOTTO, Gaudêncio; CIAVATTA, Maria. (orgs.). Teoria e Educação no Labirinto do Capital. 2ed. Petrópolis, RJ: Vozes, 2001. - Silva, Régis Henrique dos Reis (Universidade Estadual de Campinas, 2012)
Resenha